Doing adaptive management at Sida (SIDA, 2019)
Lessons from the market systems development approach The evaluation fo cuses on Sida’s management of MSD projects. The projects are applying the MSD approach with an aim to: - contribute to improved MSD programm ing by Sida through better management practices across the project cyc le - generate recommendations on how Sida can create conducive conditi ons for systems approaches and adaptive programming more generally. Th e brief assesses Sida’s organisational capacity for adaptive managemen t in three dimensions: - leadership and culture - staff capacities - s kills, and systems and procedures